Sensitivity analysis of a simplified precipitation-runoff model to estimate water availability in Southern Portuguese watersheds - Martins, Tiago N.; Mendes Oliveira, Manuel; Portela, Maria M.; Eira Leitão, Teresa (Acque Sotterranee - Italian Journal of Groundwater, 2021)
The water availability estimation in large regions is a relevant procedure to define broad water resources management policies but may prove difficult due to the lack of data and uncertainty to related regional hydrological and hydrogeological characterization. BALSEQ, a daily sequential water budget model, was applied in a set of twenty-two watersheds in southern Portugal, aiming to understand the possible relations between the model parameters and watershed characteristics that may allow assembling calibration functions for non-monitored watersheds. A sensitivity analysis was conducted by comparing BALSEQ results with measured surface flow, focusing specifically on the fraction of the potential maximum retention (?) and the maximum amount of water available in the soil for evapotranspiration (AGUT) parameters and the underlying hydrogeological conceptual model that ultimately controls the surface-groundwater interactions. The overall results did not allow to identify clear relations that permit extrapolation to other regions without data as the sensitivity analysis procedures returned similar results for wide intervals of parameters for the majority of watersheds. The results confirmed that the groundwater discharge is an important component for the total measured surface flow and that the ? parameter should not be overlooked when calculating direct runoff. Poor adjustments between the model results and measured flow were observed in watersheds with a low Surface flow – Rainfall ratio.